Construction of g-C3N4/Ag/TiO2 Z-scheme photocatalyst and Its improved photocatalytic U(VI) reduction application in water - Yuelin Liu; Yilei Yuan; Shangyuan Ni; Jun Liu; Shuibo Xie; Yingjiu Liu (Water Science and Technology, 2022)
The reduction of soluble U(VI) to insoluble U(IV) by photocatalytic technology is considered to be a valid method to remove U(VI) from water. Herein, g-C3N4/Ag/TiO2 Z-scheme heterojunction was synthesized for photocatalytic U(VI) reduction application. The SEM, XRD and XPS characterization results showed that a ternary g-C3N4/Ag/TiO2 composite photocatalyst was synthesized successfully. g-C3N4/Ag/TiO2 exhibited excellent photocatalytic reduction performance for U(VI) under visible light irradiation. After 30 min irradiation, the removal rate of U(VI) was above 99%. XPS indicated that the majority of U(VI) on the surface of g-C3N4/Ag/TiO2 was reduced to U(IV). In addition, the photocatalytic activity of g-C3N4/Ag/TiO2 has been kept significantly after five rounds of experiments, indicating good stability. g-C3N4/Ag/TiO2 exhibited better photocatalytic reduction of U(VI) under visible light irradiation, which is mainly ascribed to Z-scheme photocatalytic mechanism assisted by the LSPR effect (Local Surface Plasmon Resonance). Ag with plasmon resonance effect on the loading has a strong absorption of photon energy. In addition, an intermediate charge transfer channel is formed between Ag and the semiconductor to inhibit the combination of photogenerated electrons and holes, resulting in a significant increase in the photocatalytic activity of the photocatalyst. This idea has some significance in design of other composite photocatalytic systems. HIGHLIGHTS Z-scheme heterojunction was synthesized successfully.; g-C3N4/Ag/TiO2 exhibited excellent photocatalytic reduction performance for U(VI) under visible light irradiation.; g-C3N4/Ag/TiO2 exhibited better photocatalytic reduction of U(VI) under visible light irradiation, which is mainly ascribed to Z-scheme photocatalytic mechanism assisted by the LSPR effect.;